SOCIOECONOMIC AND TRADITIONAL IMPORTANCE OF DATE PALM - Hadrami, Abdelbasset El; Al-Khayri, Jameel M. (Emirates Journal of Food and Agriculture, 1999)
The date palm fruit is a drupe exhibiting a high diversity in texture, shape, color and chemical composition depending on the genotype, environment, season and cultural practices. The fruit typically characterize the variety. The socio-economic value of dates is particularly known from oases, where date palms grow and fruits were historically the medium of exchange between populations. The geographical distribution of date palm cultivars is not yet well studied and the international demand on some of them will have disastrous impacts on the sustainability of this crop in the long term. This impoverishes germplasm and narrows the diversity grown among oases. In addition, despite the presence of several reports on the chemical composition and the nutritional value of dates, many other potentialities of the fruits remain to be explored. Many claims report on the antibacterial, antifungal, antitumor, antiulcer and immuno-modulatory properties of dates. Recently, the antioxidant activity of some cultivars was investigated and attributed to phenolic compounds. Dates are very rich in phenolics, in quality and quantity, which opens many fields of investigation in terms of new potential uses. This study summarizes the recent progress in date research, providing an up-to-date overview of the worldwide production/commercialization and the traditional and medicinal uses. Other current and future applications of dates also are highlighted.